FRI0213 Anti-TNF therapy in refractory uveitis of behcet's syndrome. A multicenter study of 63 patients. (23rd January 2014) - Bejerano, C.; Blanco, R.; Mesquida, M.; Adán, A.; Espinosa, G.; Beltrán, E.; M-Costa, L.; Cordero-Coma, M.; Salom, D.; D-Llopis, M.; G-Serrano, J.; Ortego, N.; et al.
Abstract : Objectives: To assess the efficacy of Infliximab (IFX) and adalimumab (ADA) in refractory uveitis of Behçet's syndrome. Methods: Study of 63 patients followed in the Uveitis Clinic of 24 hospitals. All of them were refractory to conventional therapy with systemic steroids and ≥1 immunosuppressive drug. Efficacy was evaluated according to SUN criteria, and macular thickness by optical coherence tomography (OCT). Outcomes and comparisons were made at week 1, week 2, month 1, month 6 and at 1 and 2 years. Statistical analyses were performed using the STATISTICA (Statsoft). Results were expressed: mean±1SD (normally distributed variables) or median [25th-75th interquartile range-IQR] (not normally). Continuous variables were compared with the Wilcoxon test. Results: We studied 63 patients/110 affected eyes (36M, 27W), mean age 38.9±9.0 years. Prior to anti-TNF, patients had received ivMprednisolone (n=20), cyclosporine (CyA) (n=53), methotrexate (MTX) (n=31) and azathioprine (AZA) (n=30). IFX was the anti-TNF more commonly used (64%). The remaining patients (36%) were treated with ADA. 14 patients (22%) required switching (12 from IFX→ADA; 2 ADA→IFX). Dosage: IFX 5 mg/kg/iv every 4-8 weeks or ADA 40 mgsc/2weeks. The median[IQR] follow-up from the onset of anti-TNF was 36 [20-60] months. Significant improvement of Visual acuity (VA), Tyndall and vitritis was observed soon (week 1). At 2 years, VA improved from 0.5±0.3 at basal to 0.7±0.3 (p<0.001), Tyndall from a median of 1.07 [0-2] to 0.09 [0-0] (p<0.001) and vitritis, from 1.0 [0-2] to 0.0 [0-0], respectively. Initially, 17 patients (24 eyes) had cystoid macular edema (CME). Following anti-TNF OCT decreased from 320.2±120.9 to 260.4±42.8 at 2 years (p<0.001). The most serious side effect was a miliary tuberculosis in 1 patient at month 1 after the onset of IFX. Conclusions: Monoclonal anti-TNF therapy is effective and relatively safe in uveitis of Behcet's syndrome refractory to conventional therapy. Disclosure of Interest: None Declared